Within-City Variation in Urban Decline: The Case of Detroit - Guerrieri, Veronica; Hartley, Daniel; Hurst, Erik (American Economic Review, 2012)
When a city experiences a decline in income or population, do all neighborhoods within the city decline equally? Or, do some neighborhoods decline more than others? What are the characteristics of the neighborhoods that decline the most? We answer these questions by looking at what happened to neighborhoods within Detroit as Detroit experienced a sharp decline in income and population from the 1980s to the late 2000s. We find patterns of changes in income and population that are consistent with the model and empirical patterns of gentrification presented in Guerrieri, Hartley, and Hurst (2011), only playing out in reverse.